2020
DOI: 10.3390/vision4020021
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Familiarity in the Perception of Depth

Abstract: Bishop Berkeley suggested that the distance of an object can be estimated if the object’s size is familiar to the observer. It has been suggested that humans can perceive the distance of the object by using such “familiarity” information, but most or many of the prior experiments that found an effect of familiarity were not designed to minimize or eliminate potential influences of: higher cognitive factors on the observers’ responses, or the influences of low-level image features in the visual stimuli used. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…They had no spatial depth perception defects. Mischenko et al 42 demonstrated that familiarity affects depth perception. Therefore, we familiarized each participant with the experimental process and system prior to the experiment via oral or written means only.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…They had no spatial depth perception defects. Mischenko et al 42 demonstrated that familiarity affects depth perception. Therefore, we familiarized each participant with the experimental process and system prior to the experiment via oral or written means only.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…The astigmatic elongation effect becomes negligible when using a shorter focal-length camera, like NIKON18 mm and iPhone. Under the conditions, the relationship among the lens size, the photo quality, and the shooting distance is expressed quantitatively in terms of the depth of field (DOF), the zone of distances that are within acceptable sharpness defined with the circle of confusion (COC) [30][31][32]. Fig.…”
Section: Lens Size and The Depth Of Field (Dof)mentioning
confidence: 99%
“…For example, in observing the back wall of a water tank in Section 4.1, the author judged the image as image-A, or a standing and shrunken image being located at the object's position, and did not expect the possibility of it being image-B. Such perception in depth must be the familiarity cue [31][32][33]. The familiarity cue is not based on physics but on human experience of known sizes and familiar scene structures.…”
Section: Monocular Visionmentioning
confidence: 99%